Mechanical and durability properties of slag/fly ash based alkali-activated concrete reinforced with steel, polypropylene and polyamide fibers - Kuranli, Omer Faruk; Uysal, Mucteba; Canpolat, Orhan (TAYLOR & FRANCIS LTD, 2022)
In this study, mechanical, durability, and microstructural properties of fiber-reinforced slag-fly ash-based alkali-activated concretes were investigated. Polypropylene (PP), steel (ST), and polyamide (PA) fibers were used, and the mechanical properties such as compressive, tensile, and flexural behaviour were investigated. High temperature and freeze-thaw tests were carried out within the scope of durability properties. High-temperature tests were conducted at 300, 600, and 900 degrees. Freeze-thaw tests were applied in 250 cycles. Microstructural analyzes were also carried out to understand the matrix composition of fiber-reinforced slag-fly ash-based alkali-activated concrete. The fibers have improved many mechanical properties, such as tensile and flexural strength. Existing building codes have shown consistent results in predicting the compressive strength of fiber-reinforced alkali-activated concretes at high temperatures. In addition, comparisons were made using existing building codes for splitting tensile strength and flexural strength, and new models were proposed.
Keywords: Ground granulated blast furnace slag; fly ash; alkali-activated concrete; steel fiber; polypropylene fiber; polyamide fiber; high-temperature; freeze-thaw; BEHAVIOR; PERFORMANCE; TOUGHNESS; Engineering